"Happy silver anniversary": Green Chemistry at 25. Issue 1 (16th December 2015) - Anastas, Paul; Han, Buxing; Leitner, Walter; Poliakoff, Martyn
Abstract : Editorial article celebrating 25 years of the field of Green Chemistry.